Public debt and borrowing: Are governments disciplined by financial markets? - Nicolas Afflatet (Cogent Economics & Finance, 2016)
With the announcement to intervene on financial markets to restore the monetary transmission mechanism, the ECB has attenuated the pressure of the markets on the endangered peripheral countries of the Eurozone. Critics argue that by eliminating the markets' disciplining interest mechanism, governments in the crisis countries will not carry out reforms and consolidate their budgets. This kind of interplay between public deficit policy and financial markets is commonly discussed under the notion of Market Discipline Hypothesis. The hypothesis' second half suggests that governments react to rising interest rates by adjusting their deficit policy. Based on panel data for the European Union, different models are tested to investigate if governments react to rising interest rates. The results indicate that governments do raise their primary surpluses when they perceive the rising interest rates in their budgets. Governments react quite quickly to changing interest rates, although there seems to be some backlash in the medium-run.
Keywords: H62; H63; 330; market discipline hypothesis; public deficits; public debt; sovereign bond yields; Eurozone; public debt crisis